On our way [videorecording (DVD)] - Curtis, Sophie Lane, 1995-; Curtis, Sophie Lane, 1995-; Richardson, Micheál, 1995-; Powers, Keith (Actor); Dale, James Badge, 1978-; Richards, Christopher Paul, 2003-; Modine, Ruby, 1990-; Ben-Victor, Paul; Brewster, Jordana, 1980-; Nero, Franco; McCormick, Declan (Actor); Mawas, Ahmed; et al. (Gravitas Ventures, 2023)
Henry contemplates suicide while writing the end to his newest script a retelling of his past with his lost love, Rosemary. As a dark voice pushes him to the brink, Rosemary fights to make him believe in himself before it is too late.